Pengaruh Visual Merchandising dan Store Atmosphere terhadap Minat Beli Konsumen pada Toko Kosmetik di Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Jasmi Julita; Cut Mega Putri; Chairiyaton Chairiyaton (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of visual merchandising and store atmosphere on consumer purchase intention at cosmetic stores in Johan Pahlawan District, West Aceh Regency. Using a quantitative descriptive approach, the population consists of consumers shopping at cosmetic stores. Samples were determined using convenience sampling with the Cochran formula, obtaining 100 respondents. Primary data were collected through questionnaires and processed using SPSS version 23. The multiple linear regression results show a positive influence between visual merchandising and store atmosphere on consumer purchase intention. The coefficient of determination is 53%, indicating both variables explain 53% of consumer purchase intention, while 47% is influenced by other factors. The t-test results show t-count 4.612 > t-table 1.984 (sig. 0.000 < 0.05), indicating a partial influence of visual merchandising on purchase intention. The t-test for store atmosphere shows t-count 4.274 > t-table 1.984 (sig. 0.000 < 0.05), indicating a partial influence. The F-test shows F-count 54.800 > F-table 3.09 (sig. 0.000 < 0.05), indicating a simultaneous influence of visual merchandising and store atmosphere on consumer purchase intention.